2019 Global food policy report - International Food Policy Research Institute (2019)
2019 GLOBAL FOOD POLICY REPORT IFPRI The 2019 Global Food Policy Report reviews major food policy developments and events from the past year. In this eighth annual report, leading researchers, policymakers, and practitioners explore the potential of rural revitalization to improve rural lives and meet the Sustainable Development Goals.